2016
DOI: 10.1002/chem.201600280
|View full text |Cite
|
Sign up to set email alerts
|

16O/18O Exchange of Aldehydes and Ketones caused by H218O in the Mechanistic Investigation of Organocatalyzed Michael, Mannich, and Aldol Reactions

Abstract: Organocatalyzed Michael, Mannich, and aldol reactions of aldehydes or ketones, as nucleophiles, have triggered several discussions regarding their reaction mechanism. H2 (18) O has been utilized to determine if the reaction proceeds through an enamine or enol mechanism by monitoring the ratio of (18) O incorporated into the final product. In this communication, we describe the risk of H2 (18) O as an evaluation tool for this mechanistic investigation. We have demonstrated that exchange of (16) O/(18) O occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 85 publications
0
28
0
Order By: Relevance
“…(3), Figure ]. To monitor the reaction by mass spectrometry, we used 3‐(3,4‐dimethoxyphenyl)propenal ( 7 ) instead of cinnamaldehyde, and 7 was treated with amine catalyst 1 or 2 in the presence of H 2 18 O (4 equiv) and p ‐nitrophenol (10 mol %) . As the iminium ion would react with H 2 18 O to afford 18 O‐labeled aldehyde 7 , the generation of the 18 O‐labeled aldehyde reflected the generation of the iminium ion.…”
Section: Figurementioning
confidence: 99%
“…(3), Figure ]. To monitor the reaction by mass spectrometry, we used 3‐(3,4‐dimethoxyphenyl)propenal ( 7 ) instead of cinnamaldehyde, and 7 was treated with amine catalyst 1 or 2 in the presence of H 2 18 O (4 equiv) and p ‐nitrophenol (10 mol %) . As the iminium ion would react with H 2 18 O to afford 18 O‐labeled aldehyde 7 , the generation of the 18 O‐labeled aldehyde reflected the generation of the iminium ion.…”
Section: Figurementioning
confidence: 99%
“…Conversely, complete or partial retention of 16 O in the α‐functionalized carbonyl oxygen suggests an enol pathway because this mechanism does not involve a hydrolysis step. Two complications make this experiment an unreliable probe of enamine versus enol pathways: (1) explicit addition of water alters the reaction kinetics and might also change the mechanism of the specific reaction in question; and (2) Hayashi has recently shown that both the product and starting material can reversibly form enamines with amine catalysts, resulting in the generation of a statistically significant amount of 16 O water, which can lead to retention of 16 O in the product even if the enamine mechanism is operational . This suggests that, although 18 O incorporation studies can support an enamine mechanism, these experiments should be conducted and interpreted with an overabundance of caution.…”
Section: Figurementioning
confidence: 99%
“…Twoc omplications make this experiment an unreliable probe of enamine versus enol pathways:( 1) explicit addition of water alters the reactionk inetics and might also change the mechanism of the specific reaction in question; [5] and (2) Hayashi has recently shown that both the product and starting material can reversibly form enamines with amine catalysts, resulting in the generation of as tatistically significant amounto f 16 Ow ater,w hich can lead to retention of 16 Oi nt he product even if the enamine mechanism is operational. [6] This suggestst hat, although 18 O incorporation studies can support an enamine mechanism, these experiments should be conducted and interpreted with an overabundance of caution.M ore importantly,i td emonstrates the need for an additional robustquantitative probe for these sister mechanismsi na minocatalysis. We report herein the use of heavy atom ( 13 C) kinetic isotope effectsi nc onjunction with theoretical calculations as aquantitative probe to distinguish between enamine ande nol mechanismsi na minocatalysis withoutmodifyinge xperimental conditions.…”
mentioning
confidence: 99%
“…In order to determine whether the organocatalytic Michael reaction between nitroalkenes and aldehydes catalyzed by diphenylprolinol trimethylsilyl ether in water evolved through enamine or enol mechanism, Hayashi et al recently investigated this reaction in the presence of H 2 18 O, by monitoring the ratio of 18 O incorporated into the final Michael product [28]. This study demonstrated, however, that a 16 O/ 18 O exchange in the aldehyde starting material, occurring through an enamine intermediate, was faster than the Michael reaction.…”
Section: Introductionmentioning
confidence: 99%